Comparison of Selected Nutritional Analysis of Goat and Cow Milk Kefir Using Indonesian Kefir Grains - Nurul’azah Mohd Yaakub; Ahmad Izzat Muhammed Jaini; Mohamad Zaihan Zailan; Bibi Nabihah Abdul Hakim; Norliza Julmohammad (Universiti Malaysia Sabah, 2024)
Kefir is a fermented dairy beverage produced with kefir grains. It is high in probiotics and provides nutrition and health benefits. The effect of different level of kefir grains and incubation time on the chemical characteristics of goat and cow milk kefir was investigated. Kefir samples were prepared using 3 and 5% (w/v) kefir grains with incubation times of 12 and 24 hours. The addition of kefir grains significantly affected the pH, acidity, lactose, and protein content compared to control. There is no significant difference on pH, acidity, lactose, and protein in between both kefirs prepared in this study regardless of the treatments. The results showed that 5% (w/v) kefir grains with 24 hours incubation time was suggested to be the best milk kefir preparation for both goat milk and cow milk kefir.